RELIGIUSITAS DAN TOLERANSI ANTAR SlSWA BEDA AGAMA PADA SEKOLAH MENENGAH ATAS NEGERI DI KABUPATEN BANYUMAS (Studi pada SMAN 2 Purwokerto) - Muh. Hanif; Devi Idiah Astuti (Jurnal Penelitian Agama, 2017)
Abstract: There is an increase in religiosity at SMAN. The survey results of Setara Institute (2016: 12) to 355 respondents from 171 SMANs in Jakarta and Bandung showed that students' activeness to follow religious activities in school is high. A total of 50.9% of students attend activities held at school. While as many as (44.1%) students follow religious activities conducted outside the school. In detail the proportion of students attending religious activities outside school hours are: religious studies (43.3%), religious lectures (22.7%), and religious social service (14.6%). Still from the same survey from Setara Institute (2016: 12). From a survey of 242 respondents, the proportion of SMAN students attending religious activities after following the subjects at school was as follows: 27.3% followed the recitation activity; 22.3% follow mosque youth activities; 20.7% follow spiritual activities, 11.6% follow religious studies; 9.1% attend church youth activities; 7.4% follow religious activities; and 1.7% attend religious training. This data also shows high religiosity in SMAN. Keywords: Religiosity, tolerance, Senior High School